PENJAJAHAN BARAT ATAS DUNIA ISLAM (PILAR, 2022)
This article is descriptive literature review and critical analysis through a historical approach that seeks to uncover, explore, study and analyze the problems that are the subject of study from a historical perspective. The history referred to in this paper is the history of the Islamic world in the nineteenth century and the penetration of the Western world into the Islamic world and all the consequences that followed. The revival of the West leads to the treasures of knowledge and ways of thinking that have been developed by Muslims rationally.Keywords: Islamic Word, Western, Colonial